PERBEDAAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA BERDASARKAN GENDER DAN TIPE KEPRIBADIAN SENSING-INTUITION - Irfani, Sayla; Baiduri; Arif Hidayatul Khusna (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2024)
This research aims to determine the significant differences in students' mathematical creative thinking abilities based on gender and sensing-intuition personality type. This research uses a comparative research method that is ex post facto. This research was conducted in class VIII of SMPN 1 Lekok in the 2023/2024 academic year. From a population of 199, a sample of 80 was selected, namely 20 male students with a sensing personality type, 20 male students with an intuition personality type, 20 female students with a sensing personality type, and 20 female students with an intuition personality type. Data collection used creative thinking ability test instruments and sensing-intuition personality type tests. Data were analyzed using independent t-test and two-way anova. Based on the results of the analysis, it can be concluded that 1) there is no significant difference in creative thinking abilities between female and male students. 2) There are differences in creative thinking abilities between students with the sensing personality type and students with the intuition personality type. 3) There is no interaction between gender and sensing-intuition personality type on students' creative thinking abilities.